Estudo da infiltração marginal em restaurações de resinas compostas para dentes posteriores: efeito de material, preparo cavitário e condicionamento do esmalte a nível cervical - Araújo, Rosehelene Marotta [UNESP] (1989)
For many years the dental profession has sought an esthetic material to replace the amalgam alloys. Recently composite resins for posterior teeth have been introduced into the marketplace. The manufacturers claimed that these materials are indicated for stress-bearing restoration. However. such resins have presented some limitations such as marginal leakage which has great clinical importance because it is responsible for postoperative sensitivity, and occurence of secundary caries followed by pathological changes of the pulp. The purpose of this ''in vitro'' study was to investigate the cervical marginal leakage in class II restorations with chemically cured resin - PlO - and light- cured resin - P30 - in two types of cavities: conventional and adhesive. The effect of acid-etching in this area was also observed. The cavities were prepared in premolar teeth, recently extracted for orthodontic purposes, using a Microscope Modified by GABRIELLI and cols.25, in order to obtain standardized cavities. Dentine adhesive (Scotchbond) was used in all experimental groups Leakage was evidenced by Rodamina B dye penetration after thermocycling procedure between 10°C and 50ºC temperature and analysed according to HIRSCH g WEINREB modified criterion by using ZEISS Stereoscopic Magnifying Glass (10x). According to the results, we should concluded that: 1- Cervical marginal leakage occurred to 77,5% of conventional cavities restorations and 47,5% of adhesives cavities. 2- The major percents of leakage, regardless the factors studied, always occurred at level 3, that is, with leakage up to axial wall. 3- Either chemically cured resin or light – cured resin presented the same leakage. 4- The acid-etching reduced from 70% to 55% the leakage percentage observed. 5- The leakage observed for adhesive or conventional cavities continued when chemically cured resin or light- cured resin was used. 6- Acid-etching...